Numerical simulation of blood flow in centrifugal heart pump by utilizing meshless smoothed particles hydrodynamic method - Rahmanian, E.; Navidbakhsh, M.; Mohammadzadeh, M.; Habibi, Hamed (2015)
© 2015 SERSC. Numerical methods have had a tremendous effect in optimization of heart devices. Among all methods meshing independentalgorithms, as modern methods in simulations, have solved most problems related to meshing and reduced its complexity. In this paper, blood flow in heart centrifugal pump is simulated by dynamic of particles and based on this model, governing equations of velocity field and stress distribution, are determined. Also, the harmful locations in which hemolysis and thrombosis occur, are detected. In the present work we explore the feasibility of performing computations of such flows using SPH.To evaluate the accuracy of the computations the results are compared to other researches in [7,4].The analysis results can also be used as the basis for further researches and the improvement of centrifugal pump.